Problems of Humanitarian Discourse in Modern Philosophies - Ruptash, Olga; Filyanina, Nelya; Chitishvili, Viktoriia; Rudenko, Olga; Sinelnikova, Valentyna (MAGNANIMITAS, 2021)
The urgency of intelligence involves understanding the importance of the concept of modern philosophy of science and the problems of humanitarian discourse in terms of their internal correlation, also focused on social problems. On this basis, modern philosophy of science and the problems of humanitarian discourse require detailed study, as they describe a comprehensive view of the nature of scientific knowledge, the development of which created our current civilization and had a huge impact on the formation of modern culture. The article identifies the components of modern philosophy of science (historical and philosophical section, ontology, philosophical anthropology, epistemology (theory of knowledge) and social philosophy).
Keywords: Humanitarian Discourse, Mode of Scientific Cognition, Philosophy of Science, Problems of Cognition